THE EFFECT OF MAGNESIUM ON HUMAN HEALTH - Nodira Fayziyeva (Innovate Conferences, 2025)
Magnesium is a vital macro-mineral that plays a central role in numerous biochemical and physiological processes essential for human health. It acts as a cofactor in over 300 enzymatic reactions related to energy metabolism, neuromuscular function, protein synthesis, and nucleic acid stability. Adequate magnesium levels are crucial for maintaining cardiovascular health, regulating blood pressure, and supporting bone integrity. Deficiency in magnesium has been associated with a wide range of chronic disorders, including type 2 diabetes, hypertension, osteoporosis, and depression. Recent scientific evidence also highlights the anti-inflammatory and neuroprotective properties of magnesium, suggesting its potential therapeutic role in preventing metabolic and neurodegenerative diseases. This article explores the physiological significance of magnesium, its impact on various organ systems, and the clinical consequences of magnesium deficiency in humans.
Keywords: Magnesium; human health; metabolism; cardiovascular system; bone health; deficiency; inflammation; neuroprotection; chronic diseases.